ANALYSIS OF THE INFLUENCE OF SOCIAL MEDIA TO BRAND EQUITY ON CUSTOMER SATISFACTION AND DECISION OF ZERO TO ONE - Ditania Tiara Imrohati; Harjum Muharam (Faculty of Economics and Business Diponegoro University, 2022)
As a business accelerator, Zero to One provides services to help many startups to grow with a tailored approach. However, the company's customer base has shrunk, and the social media platform's performance has suffered significantly. As a result, Zero to One expected that analyzing the influence of social media on brand equity could be a way to show their branding in a broader market and introduce it to the Northern Netherlands. To answer the main question, qualitative research will be used in this research. Researchers took the decision to conduct interviews about the company's situation. Researchers obtain secondary data from various credible sources. Furthermore, data from interviews with other start-up companies regarding their demand in branding and marketing will be used to collect primary data. Secondary data obtained from studies, surveys, or tests conducted by others or for other research are used to answer questions. The findings identify the relationship between social media sharing elements that influence brand association and brand equity. Based on the results of the study, it is known that social media has affected Zero to One's brand equity, although not as a major aspect in influencing purchasing decisions. However, the results show that social media is still the best choice to increase Zero to One's brand equity.